Physicochemical and thermodynamic properties of imidazolium ionic liquids with nitrile and ether dual functional groups - Raj, J.J. (Elsevier B.V., 2017)
Synthesis of new dual functionalized imidazolium ionic liquids (ILs) containing nitrile functionality and ether group were synthesized and characterized. Bis(trifluoromethylsulfonyl)imide, trifluoroacetate and dicyanamide were used as the anion. The combination of two functional groups on an imidazolium cation was mainly developed to assess their potential in desulfurization of fuel oil. Although ILs based on this individual functional group has been reported to improve the desulfurization efficiency, no effort has been made to combine nitrile and ether functional groups on the same cation to enhance the desulphurization potential. In this report, we tailored both nitrile and ether functionality on imidazolium cation and studied their physicochemical properties in details. NMR (1H and 13C) spectroscopy and elemental analysis were used to characterize the synthesized ILs. Physical properties and optical properties of the ILs were investigated in a wide temperature range. The synthesized ILs showed good thermal stability. COSMO-RS was effectively utilized to discuss the σ surface, σ potential and σ profile of the synthesized ILs. © 2016 Elsevier B.V.